2010
DOI: 10.5195/ehe.2010.12
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Access and Equity in Tertiary Education: The Case of Indonesia

Abstract: How does an individual choose to pursue tertiary education in Indonesia in an era of mass tertiary education? What factors affect this decision? In thisarticle, we analyze the determinants of access to tertiary education in Indonesia from the demand side using household survey data. We also examine theimpact of regional and family background factors on inequity of access to tertiary education. In order to analyze the demand side factors for tertiaryeducation, we use a multi-nominal logit model to examine what … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
4
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
6
4
1
2
Order By: Relevance
“…Chen (2009) and Ogawaa & Iimuraa (2010) have a similar finding with us. They find that head of households' education have a positive and significant effect to the probability of the children pursuing tertiary education.…”
Section: Discussionsupporting
confidence: 84%
“…Chen (2009) and Ogawaa & Iimuraa (2010) have a similar finding with us. They find that head of households' education have a positive and significant effect to the probability of the children pursuing tertiary education.…”
Section: Discussionsupporting
confidence: 84%
“…For family who can't afford, it will give the confidence for the high intelligence individual by hoping that they can give return after tertiary education. The result of this research is similar with previous research which was done by Hansen et et al (1989), Ogawa and Iimura (2010) and Jimenez and Velasco (2000).…”
Section: Multinomial Logit Regression Analysis and Risk Relative Ratisupporting
confidence: 92%
“…The occupational status while taking secondary education has a positive and significant impact on the demand for diploma education. The results of the study found by Ogawa and Iimura (2010) are in contrast to the hypotheses that have been compiled. The occupational status variables have a positive impact on the demand for undergraduate education in urban or urban models.…”
Section: B Occupational Status While Taking Secondary Educationcontrasting
confidence: 84%
“…Il existe un important corpus de recherche, qui mesure l'inégalité du degré d'instruction à tous les niveaux de l'enseignement. Clancy et Goastellec (2007), Ogawa et Iimura (2010) et Koucky, Bartusek et Kovarovic (2010) -quelques auteurs parmi d'autres qui se sont penchés sur la question de l'équité dans l'enseignement supérieur -affirment qu'une analyse comparative des définitions données à l'accès et à l'équité et des politiques fondées sur ces définitions permet de faire ressortir les différences et les points communs entre les pays. Cependant, les études comparatives de l'inéquité entre pays en rapport à l'accès à l'enseignement supérieur et aux niveaux d'instruction atteints dans l'enseignement supérieur sont rares, avec seulement quelques études notables, telles que celles de Thomas, Wang et Fan (2001), Zhang et Li (2002), Barros et al (2009), et Koucky, Bartusek et Kovarovic (2010).…”
Section: éQuité En Matière D'éducationunclassified